2022
DOI: 10.3390/ijerph19052803
|View full text |Cite
|
Sign up to set email alerts
|

“Time Does Not Heal All Wounds”: Sexual Victimisation Is Associated with Depression, Anxiety, and PTSD in Old Age

Abstract: Sexual violence (SV) has an important impact on mental health. Childhood sexual abuse is linked to internalising disorders in later life. In older adults, SV occurs more often than previously believed. Moreover, health care workers lack the skills to address SV in later life. Studies researching the mental health impact of lifetime SV, i.e., SV during childhood, adulthood, and old age, are lacking. Between July 2019 and March 2020, 513 older adults living in Belgium participated in structured face-to-face-inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…These numbers are higher compared to the prevalence estimates in community‐dwelling older adults, which ranged from 4% to 23% for depressive symptoms, 1%–7% for anxiety, and 2.5% and 4% for PTSD 45‐47 . Our results are in line with previous studies suggesting that sexual victimisation is linked with adverse mental health outcomes in later life 9,15,16 . Regarding suicide attempts our sample showed higher prevalence rates compared to community samples.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…These numbers are higher compared to the prevalence estimates in community‐dwelling older adults, which ranged from 4% to 23% for depressive symptoms, 1%–7% for anxiety, and 2.5% and 4% for PTSD 45‐47 . Our results are in line with previous studies suggesting that sexual victimisation is linked with adverse mental health outcomes in later life 9,15,16 . Regarding suicide attempts our sample showed higher prevalence rates compared to community samples.…”
Section: Discussionsupporting
confidence: 84%
“…[45][46][47] Our results are in line with previous studies suggesting that sexual victimisation is linked with adverse mental health outcomes in later life. 9,15,16 Regarding suicide attempts our sample showed higher prevalence rates compared to community samples. Around 5% of sexually victimised older adults in our study reported a suicide attempt during lifetime compared to 2.6% in a community sample of adults aged 75 years in older in Flanders.…”
Section: Of 12mentioning
confidence: 62%
See 2 more Smart Citations
“…Hence, it is never too late to disclose or seek professional help upon SV. Given the high prevalence numbers of SV in older adults, both during lifetime and in the past 12-months, and the important mental health impact of sexual victimization in old age (Ege, 2015;Nobels et al, 2021bNobels et al, , 2022aRapsey, 2019), we recommend a routine inquiry about sexual victimization in all older adults with mental health problems. However, research has shown healthcare workers do not feel comfortable discussing SV with older adults (Goldblatt et al, 2020;Gott et al, 2004;Saunamäki & Engström, 2014).…”
Section: Implications For Clinical Practicementioning
confidence: 99%